THE IMPORTANCE OF LOGIC IN UNDERSTANDING ISLAMIC SCIENCES (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the importance of logic in understanding and studying Islamic sciences. Logic is analyzed as a methodological tool that protects human thinking from error and ensures systematic reasoning. The study explores the role of logic in major Islamic disciplines, including tafsir, fiqh, and aqidah. It highlights how logical principles contribute to the interpretation of Qur’anic texts, the derivation of legal rulings, and the defense of theological doctrines. The article also discusses the views of Muslim scholars regarding logic and evaluates its benefits and limitations in Islamic scholarship. The findings demonstrate that logic serves as an essential instrument for accurate analysis, critical thinking, and the sound comprehension of religious knowledge.
Keywords: Logic, Islamic sciences, tafsir, fiqh, aqidah, qiyas, reasoning, Islamic scholarship, methodology, critical thinking.